Chemical recycling of waste pet into polyester polyol for the production of semi-rigid pu foams / Asmalina Mohd Darus - Mohd Darus, Asmalina (2013)
One of the biggest problems caused by soft drink poly(ethylene terephthalate) PET bottles is the waste problem resulting in environmental pollution. To economically reduce this waste, this study presents a method to recycle the PET bottle by glycolysis and convert it into a polyester polyol that can be used to make polyurethane foam. Common soft-drink PET bottles were glycolysed by glycerol in the presence of zinc acetate as a catalyst. Dependence on glycolysis conversion on reaction temperature and the Arrhenius plot, activation energy obtained of 36.5 kJ/mol. The new polyester polyols namely glycolysed PET have hydroxyl value of 500-800 mg KOH/g. Miscibility of the glycolysed PET with a commercial polyol designated for flexible polyurethane foam synthesis was investigated. The result helps in estimating the appropriate amount of glycolysed PET in the polyol mixture. Certain amount of surfactant, catalyst and blowing agent were then added in the preparation of polyol component before reacting with MDI in the formation of polyurethane (PU) foam. Results showed that the semi-rigid polyurethane foams obtained have density of 50-90 kg m-3, with open cell content and good compression strength in the range of 90-120 kPa and comparable with other studies. The polyurethane foams synthesized could be used in automotive applications such as insulation materials.